Microscopy‐Based Assessment of Fatty Acid Uptake and Lipid Accumulation in Cultured Cells. Issue 12 (26th December 2022) - Khan, Danish; Ara, Tarannum; Munjal, Aastha; Mishra, Sneha; Sundaresan, Nagalingam Ravi
Abstract: The heart relies predominantly on the use of fatty acids to derive energy. Metabolic disorders such as obesity, insulin resistance, and diabetes pose a major risk factor for the development of heart failure. Dysregulation of lipid metabolism observed in these diseases manifests as cardiac lipotoxicity, and is associated with cardiac dysfunction. The alarming rise in the incidence of these metabolic disorders warrants the need for tools to investigate the underlying molecular mechanisms. In this article, we describe a confocal microscopy–based approach to monitor fatty acid uptake and lipid accumulation in vitro, in neonatal murine cardiomyocytes and H9c2 cells. The protocol for assessment of fatty acid uptake relies on the use of BODIPY FL C 12™ to study the kinetics of fatty acid uptake via real‐time imaging of fatty acid uptake in live cells. Importantly, it circumvents the need for radioactive labeling of fatty acids to evaluate their uptake. Similarly, the protocol for assessment of lipid accumulation relies on the use of BODIPY™ 493/503 to stain the cytosolic neutral lipid population in fixed cells. We couple these confocal microscopy–based approaches with fluorescence intensity analysis using FIJI to quantify fatty acid uptake and lipid accumulation in vitro . © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Assessment of fatty acid uptake Basic Protocol 2 : Assessment of lipid accumulation